The Role of Political Identity and Media Selection on Perceptions of Hostile Media Bias During the 2012 Presidential Campaign. Issue 3 (2nd July 2016) - Lin, Mei-Chen; Haridakis, Paul M.; Hanson, Gary
Abstract : Viewing a hostile media bias against one's group (e.g., political party) is a perceptual effect of media use. When it comes to the portrayal of political parties in the United States, prior research suggests that both Democrats and Republicans see mainstream media coverage as favoring the other side, regardless of the orientation of the political news coverage. Although prior research has not identified all factors that make this perceptual bias more likely, or at explaining how or why this perceptual effect occurs, we do know that it is related to one's group identity. In this study, we examined salient predictors of hostile media bias during the 2012 presidential campaign. Individual (i.e., political cynicism) and group identity related (i.e., group status, intergroup bias, political ideology) differences of media users predicted such perceptions. But, the medium selected for political information about the campaign also mattered. The use of two media in particular—TV and social networking sites—appear to have blunted hostile media bias perceptions, whereas the use of two other media—radio and video sharing sites—appear to have accentuated perceptions that the media were biased against one's party